FAKTOR-FAKTOR PENINGKATAN TERJADINYA KECELAKAAN KERJA DI BAGIAN PRODUKSI DI PT.JOHAN KABUPATEN KAMPAR TAHUN 2016 - Rizki Rahmawati Lestari (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2017)
Every activity that involves humans, machines and materials that can produce hazards with different differences that can cause accidents and work. There are several things that can be done to overcome accidents, namely: elimination, substitution, technique, administration, and personal protective equipment. This study is to determine the factors of accidents working in the production section of PT. Johan Kampar Regency in 2016. This type of research is quantitative with cross sectional method. This research was carried out in the production section of PT. Johan in May 25 to 2 June 2016. Samples in this study were 43 respondents. The sampling technique used total sampling, data was collected by questionnaire and research data using Univariate data and Bivariate test, Bivariate test using Chi Square test. From the results of the study showed that there was a relationship between PPE (P Value = 0.001), OR = 14.25; the risk of using PPE (P value = 0.002), OR = 2.316; Participation training (P value = 0.001), OR = 5.225 for the incidence of work accidents at PT. Johan, Kampar Regency in 2016. So that PT. Johan conducts supervision and training to deal with injuries and provides training to workers to increase knowledge and work skills to reach zero accidents.